The Russians Are Here (The Strategic Review for Southern Africa, 2022)
Russia’s war on Ukraine inaugurated the new Cold War most feared, and some wanted. It demanded that countries pick sides. African countries and their elites have been reluctant to do so, not least because for some their food or energy supplies will be affected, while for others Putin’s authoritarian governance model is seductive. Other countries and movements are reluctant to weigh in for fear of being swept up in an elite-serving great power conflict using Ukraine as its proxy and that the invasion exposes hypocrisies. More than anything, peace and a more humane future - another kind of world, underlined not by great power competition, but solidarity binding ordinary people across borders - is even more elusive.